2012
DOI: 10.1016/j.jviscsurg.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative adhesions after digestive surgery: Their incidence and prevention: Review of the literature

Abstract: The prevention of postoperative adhesions is an important public health goal, particularly in light of the frequency of this complication. The routine use of anti-adhesion products is not recommended given the lack of studies with a high level of evidence concerning their efficacy and safety of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
118
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 81 publications
0
118
0
8
Order By: Relevance
“…How- ever, several studies have reported negative results of Seprafilm [15][16][17][18] . Studies have described how Seprafilm was not useful in preventing BO, although it was effective in preventing adhesion 15,18) . In our study, Seprafilm was effective in preventing BO after colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How- ever, several studies have reported negative results of Seprafilm [15][16][17][18] . Studies have described how Seprafilm was not useful in preventing BO, although it was effective in preventing adhesion 15,18) . In our study, Seprafilm was effective in preventing BO after colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Various products and postoperative management procedures have been used to prevent postoperative peritoneal adhesions [1][2][3][4][5][6][7][8] . The usefulness of the absorptive anti-adhesion barrier film Seprafilm [9][10][11][12][13][14] has been shown by many randomized control studies and meta-analysis, although studies with negative results do exist [15][16][17][18] . Interestingly, the reports on peritoneal adhesion or BO associated with laparoscopic surgery, the use of which has rapidly spread in recent years, are few compared with reports on open surgery 11,[19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, those advocating urgent surgery for AIO also note that approximately 60% of all cases could be improved without surgery [5]. Conservative management of AIOs is also widely applied in adult age groups [11]. The incidence of intestinal injury and recurrent adhesions following operations performed for adhesive intestinal obstruction have been reported from 11-52% (5,10,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…While the conservative treatment of nasogastric decompression can be uncomfortable for the patient, the postoperative complications from adhesiolysis can be catastrophic. Paralytic ileus, wound infection, chronic abdominal pain, and enterocutaneous fistula from iatrogenic enterotomy are all within the spectrum of complications [9]- [11]. Therefore it is critical to identify a way to minimize the peritoneal adhesion burden after initial laparotomy.…”
Section: Discussionmentioning
confidence: 99%